Immortality: A Study of Human Nature and Consciousness - Yohanes Slamet Purwadi (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2025)
The hypothetical idea of immortality or eternity has stirred human curiosity throughout civilization. There are various postulates built about immortality: they can be philosophical or scientific in nature. The arguments can be philosophical, theistic, or even rational-scientific. However, due to the development of science and technology, the issue of immortality is no longer just a religious discourse.The issue that has emerged is that these days, scientifically, factual death is understood as the “loss of information” along with the disappearance of consciousness.Thus, through science, especially visionary science, the idea has emerged to transform the content of consciousness through digital machines where consciousness, in turn, is reset and then preserved as digital information.Visionary science also encompasses the cosmic dimension of consciousness that enriches the dynamical reflection of immortality.Thus, a new stage in the understanding of immortality like this challenges public awareness and further analysis. In the context of such discourse, the aim of this research is to explore and examine arguments from both philosophical and visionary scientific perspectives that contextualize the discourse of immortality. Counterarguments are also presented, especially from assumptions related to the digitalization of consciousness. The method used in this research is the literature study method. Data collection includes data from philosophical literature and visionary science. The research results on the discourse of immortality, contemplated philosophically and cosmically, reveal that within the nature of humans themselves lie metaphysical signals for immortality, and this is explored by philosophy. Then, through the efforts of visionary science, the optimism of designing digital consciousness reveals a scientific spirit of this century, although it seems to deal with heavy or controversial challenges. However, through all this study, it is increasingly realized that human nature and consciousness can be deep rational basis for the analysis of immortality